Chemical and isotopic characterization of size-fractionated organic matter from cryoturbated tundra soils, northern Alaska - Xu, C. H.; Guo, L. D.; Ping, C. L.; White, D. M. (Journal of Geophysical Research-Biogeosciences, 2009)
Recent studies indicate a second layer of organic matter often accumulates in the lower active layer and upper permafrost in arctic tundra soils as a result of cryoturbation. In this study, cryoturbated organic matter was characterized using a combination of physical size fractionation and modern analytical techniques for elemental composition (C and N), stable isotopes (delta(13) C and delta N-15), radiocarbon content (Delta C-14), and molecular fingerprinting (pyrolysis-gas chromatography/mass spectrometry, Py-GC/MS). The results indicated that cryoturbated organic matter could be highly bioavailable. Soil organic matter (SOM) associated with fine sand particles was considered to be the organic carbon pool most sensitive to the changing climate. More organic matter is stabilized on clay minerals in arctic tundra soils compared to those in temperate and tropical soils. The bioavailable soluble organic matter extracted from cryoturbated soil was found to have significant long-term effects on carbon cycling. The similar molecular composition between cryoturbated and surface soil organic matter suggests that the vegetation cover has not significantly changed since the early Holocene. Furthermore, the SOM quality in moist acidic tundra was found to be higher than that of wet nonacidic tundra. With thawing permafrost and a deepening of the active layer, cryotrubated organic matter could reenter the biogeochemical cycles in the Arctic, resulting in a positive feedback to climate change.
id: 1828; 475IS Times Cited:0 Cited References Count:61Y

Mobilization pathways of organic carbon from permafrost to arctic rivers in a changing climate - Guo, L. D.; Ping, C. L.; Macdonald, R. W. (Geophysical Research Letters, 2007)
[1] Arctic warming may cause the release of vast amounts of soil organic carbon (SOC) from permafrost, which will manifest itself in the fluxes and composition of organic carbon in northern rivers and Arctic coastal regions. To elucidate the transport pathways of SOC, radiocarbon composition was measured for dissolved organic carbon (DOC), particulate organic carbon (POC), sediments and SOC from the Mackenzie, Sagavanirktok, and Yukon river basins, and soil leaching experiments were conducted. The radiocarbon ages of riverine suspended POC and sediments ranged from 4430 to similar to 7970 yr BP, while DOC was much younger (390-1440 yr BP) except samples from the Sag River. Soil leaching experiments released
id: 773; 187WS Times Cited:23 Cited References Count:29Y

Pedological properties of the eroding coastline along the Beaufort Sea, Alaska - Ping, C. L.; Dou, F.; Jorgenson, G.; Michaelson, J.; Lynn, L. A.; Shur, Y.; Kanevsky, M. (Eos Trans. AGU Fall Meeting Supplement, 2006)
id: 1002